2013
DOI: 10.5539/gjhs.v6n1p181
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Infertility Treatment: An Integrated Study

Abstract: Background:Infertility is one of the most important events in life. Despite the negative impact of infertility, a significant number of women struggling to conceive do not consult a physician and do not fallow up infertility treatment. This integrated study aimed to investigate a large amount of factors which influenced discontinuation of infertility treatment.Methods:This integrated study (qualitative – quantitative study) was done on infertile women who had referred to infertility center in Jahrom University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…In addition, time off and moral support were the most common resources for residents undergoing infertility treatment, but few programs provided financial support, even though high costs are a major barrier for trainees. 32 Trainees with infertility are burdened with medical school debt, low salary, and an intense schedule, further discouraging them from pursuing treatment. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, time off and moral support were the most common resources for residents undergoing infertility treatment, but few programs provided financial support, even though high costs are a major barrier for trainees. 32 Trainees with infertility are burdened with medical school debt, low salary, and an intense schedule, further discouraging them from pursuing treatment. 33 …”
Section: Discussionmentioning
confidence: 99%
“…In the South Asian subcontinent, infertility is associated with social stigma and infertile couples often face harassment and ostracism. While the women are mostly blamed and bear the brunt of social isolation and abuse, in some cases men also face ridicule and humiliation ( Mosalanejad et al , 2013 ). While the psychosocial ramifications of infertility in the South Asian continent are significant, providing access to fertility treatment is lower down the priority list for health policy makers owing to limited healthcare resources.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown only half of infertile couples in the US are able to afford treatment (Inhorn & Patrizio, 2015;Kessler et al, 2013), with little progress for the uninsured or underinsured (Berger et al, 2013). Financial burden may be a main factor that contributes to treatment delay or dropout (Mosalanejad et al, 2013;Zargham-Boroujeni et al, 2014). One of our participants poignantly said, "It's not a 'want.'…”
Section: Discussionmentioning
confidence: 98%